High Potential of Herbal Plant Extracts for Skin Protection from Ultraviolet Radiation - Le, Tien Xuan; Dang, Phuong Yen; Tran, Uyen Khanh Nguyen; Nguyen, Nhu Quynh Trung; Tran, Thanh Truc (Universitas Gadjah Mada, 2025)
This research is dedicated to exploring the photoprotective qualities of extracts from 10 different herbal plants to identify natural ultraviolet (UV) filtering agents suitable for use in cosmetics. The study pinpointed specific plant parts that showed promising photoprotective capabilities, including the fruits of Gardenia jasminoides L., the flowers of Chrysanthemum morifolium Ramat., as well as the leaves of Camellia sinensis L. and Moringa oleifera L. Among these, G. jasminoides extracts stood out for their superior photoprotection. Specifically, G. jasminoides led with an impressive in vitro SPF of 40.8 ± 0.2, with C. morifolium, C. sinensis, and M. oleifera trailing closely. Hence, the extracts were added to the base of the lotion cream to evaluate the stability and photoprotective activity. Additionally, even though natural extracts cannot completely replace conventional UV filters, they have substantially decreased the reliance on physical or chemical UV filters. Thus, this study provides a strong foundation for natural antioxidants' status and potential use for UV filtration.